The Future of Design Methodology - Birkhofer, Herbert (Springer London : Imprint: Springer, 2011)
The Future of Design Methodology gives a holistic overview of perspectives for design methodology, addresses trends for developing a powerful methodical support for design practice and provides a starting point for future design research. The chapters are written by leading scientists from around the world, who have great expertise in design methodology, as well as the farsightedness needed to develop design methodology further. The Future of Design Methodology is a detailed contribution to consolidated design methodology and design research. Instead of articulating the views of one scientist, it provides a comprehensive collection of perspectives and visions. The editor highlights the substantial deficiencies and problems of the current design methodology and summarizes the authors' findings to draw future-oriented conclusions.  The comprehensive overview of the status of design methodology given in The Future of Design Methodology will help enhance the individual scientific development of junior researchers, while the authoritative perspectives on future design methodology will challenge the views of experts. It is suitable for readers working in a wide range of design fields, such as design methodology, engineering design and industrial design.